Evaluation of balance and orthotic gait training techniques for rehabilitation in hemiplegic stroke patients - Sidra Tariq; Asim Waris; Javaid Iqbal; Niaz Bahadur Khan; Syed Omer Gilani; Shafaq Mushtaq; Qasim Awais; Khurram Mushtaq (Scientific Reports)
Abstract Stroke-induced hemiplegia is a major cause of long-term disability, often leading to lower limb deformities and abnormal gait. Ankle-foot orthoses (AFO) have shown effectiveness in improving these conditions, but limited research explores the benefits of combining AFO therapy with balance training. This study aimed to explore the effects of combining balance training exercises with orthotic intervention on various gait characteristics in stroke patients with lower limb paralysis. This randomized controlled trial (RCT) involved 32 patients, 12–18 weeks post-stroke, randomized into two groups: balance training only (n = 16) and balance training with orthotics (n = 16). Gait performance was evaluated at baseline and post intervention using the Timed Up and Go Test (TUG) and 10-Meter Walk Tests. The combination therapy group showed significant improvements in gait parameters. For the 10-Meter Walk Test, the mean pre-intervention speed was 0.31 ± 0.03 m/s, and post-intervention speed was 0.40 ± 0.03 m/s. In the TUG test, mean pre-intervention time was 27.04 ± 2.04 s, and post-intervention time was 20.55 ± 2.30 s (p < 0.05). These improvements were greater than those observed in the balance-only group. The combination of balance training and AFO therapy significantly improves gait in chronic hemiplegic stroke patients. This approach offers a promising rehabilitation strategy to enhance functional mobility and quality of life in stroke survivors.